Islamic Bureaucracy in the Philosophy of Public Administration: A Narrative Literature Review - Alfian; Endang Larasati Setianingsih; Kismartini; Tri Yuniningsih (HM Publisher, 2022)
This study aimed to analyze bureaucracy and public administration with an approach to Islamic values about norms, ethics, and marsalah mursalah as the spirit of the law. Islam still pays attention to the reality of society, thus giving birth to a humanist and authoritative formulation of Islamic law instead of authoritarianism of Islamic law. The method used for this study is a literature study. This study can be integrated with Maqhasid Syariah, namely by exploring philosophical values (the theory values), norms, and ethics related to bureaucracy and public administration in Islamic law. A number of theories recognize that Islamic values also influence public administration, such as performance, ethics, and accountability. The conversion of Islamic principles and following the secular path will result in the failure of Muslim societies and social renewal, requiring a return to Islam. In conclusion, the legitimate form of bureaucracy and public administration in the Islamic world is not only academic interests but also political interests on a global scale.